2020
DOI: 10.3389/fpubh.2020.563325
|View full text |Cite
|
Sign up to set email alerts
|

Family Structure and History of Childhood Trauma: Associations With Risk-Taking Behavior Among Adolescents in Swaziland

Abstract: Introduction: Risk-taking and self-harm behavior among adolescent are a global challenge. This study explored family structure and history of childhood trauma and their association with risk-taking and self-harm behaviors among adolescents in Swaziland. Methods: Using a cross-sectional design, a sample of 470 male and female adolescents were sampled through simple random sampling from selected high schools in Swaziland. They completed a questionnaire assessing family structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Moreover, dysfunctional households and parental involvement in risk behaviors emerged as notable predictors of subsequent risky behavior. [39][40][41][42][43] The current study reveals that women experienced a lack of financial resources in childhood, and more verbal abuse compared to men. During childhood, women have to depend on parents for all financial needs, and many instances of differential treatment for male and female children within the family are also reported.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, dysfunctional households and parental involvement in risk behaviors emerged as notable predictors of subsequent risky behavior. [39][40][41][42][43] The current study reveals that women experienced a lack of financial resources in childhood, and more verbal abuse compared to men. During childhood, women have to depend on parents for all financial needs, and many instances of differential treatment for male and female children within the family are also reported.…”
Section: Discussionmentioning
confidence: 65%
“…Regarding family conditions, environmental and genetic factors should be considered equally. We suspected that family structure, relationships between one's parents, as well as their parenting styles were mainly environmental, which were significantly different between the “traumatic” and “non‐traumatic” groups (see Table 1) (LeMoult et al, 2020; Maepa & Ntshalintshali, 2020; Whitaker et al, 2021). There was a significant difference in family history of mental illness between the two groups, suggesting that childhood trauma can be predicted by genetic factors (Vannucci et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Grounded in the challenges with the issue concerning family functioning (e.g., family breakdown or dysfunction), the adverse effect on adolescent's well-being is anticipated. Maepa and Ntshalintshali (2020) showed that the absence of a healthy balance between families, regardless of the presence of the mother or father, will potentially lead to a negative influence toward adolescents, which includes the development of risk-taking attitudes. Azmawati et al (2015) suggested that the development process has affected families in various ways.…”
Section: Introductionmentioning
confidence: 99%